The Effect of the Project-Based Learning Model with Digital Learning Media on Science Literacy and Numeracy Skills in Madrasah Ibtidaiyah - Masnia, Luluk; Suratno, Suratno; Prastiti, Tri Dyah; Utomo, Anjar Putro (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Literacy skills are one of the important aspects of education in Indonesia that should be prioritized from the primary level. Science literacy and numeracy to build critical thinking skills and help face global challenges in the 21st century. This study aims to analyze the effect of the Project-Based Learning (PjBL) model with digital learning media on science literacy and numeracy skills of fifth-grade students of Madrasah Ibtidaiyah in East Java Province through a quasi-experimental method. Through cluster random sampling, 61 students were assigned to three research classes: two experimental and one control group. Test questions, questionnaires, observation sheets, and interviews were used as instruments in this study. Data processing was done using a normality test, homogeneity test, and hypothesis testing using ANOVA. The study results showed a significant value of 0.000 for science literacy and 0.005 for numeracy literacy. Based on the test results of science literacy and numeracy skills, the average value of the class given the PjBL model learning with digital-based learning media is superior to other research classes. So, the PjBL model with digital-based learning media affects students' science literacy and numeracy skills.